Gestão da informação apoiada na gestão por processos em maternidade de alto-risco - Costa, Gustavo Resende da (2020)
Facing the problems of Information Management (IM) in Emergency Tocogynecology (ET), to proceed with the situational diagnosis and measurement of the patients’ waiting time for Medical Assistance (MA), the nurses transcribe the Reception with Risk Rating (RRR) data in an Excel spreadsheet specifically prepared for this purpose. Consequently, the stratification of this information causes rework for the teams and demonstrates impacting the quality of the information, due to failures resulting from the execution of the process. Furthermore, the problems related to IM interfere with workflows, which highlights the need to improve Process Management (PM) in Maternity. Objective: To use IM as a support to the PM in high-risk maternity ET. Methods: It was interviewed 21 professionals that totally or partially develop their assignments in ET. After the content analysis, it was conducted the processes mapping, whose steps included the macro-process design; selection of the critical process and detailed design of the current process; identification of disruptions and possibilities for improvement; the PM proposal; setting a list of requirements; and finally, the prototyping of the Information System (IS). Results: The RRR process proved to be the most critical of ET’s urgent and emergency assistance macro-process. A large number of errors and a lack of standardization in the records related to the RRR data were identified. There were cases of patients in which the waiting time for the MA was longer than that established for the clinical priority, without them having gone through the withdrawal. Commonly, it was developed activities that result in the rework of the team. In addition, it was noticed that the work processes are not integrated and that the evaluation of quality of the information in the RRR form proved to be average. Conclusion: The PM provided that there was a strategic planning in ET, through the 5W1H, the proposal of improvements to the RRR process, the GUT Matrix, the design of the RRR process, the perspective of the performance of each professional in the redesign of the RRR process, the optimization of the human resources and the lead time. Overcrowding affects the assistance flows in the maternity department and other places, either by the RRR or cancellation of surgeries for the admission of patients to other units of the institution. Moreover, with the specification of the problems, needs, and requirements of the IS, it was possible to design the prototype of the IS focused on patient data management, called “Gestão de Dados de Pacientes – Hospital Universitário” (GDP-HU).